Quinazoline‐Based Thermally Activated Delayed Fluorecence for High‐Performance OLEDs with External Quantum Efficiencies Exceeding 20%. Issue 9 (20th February 2019) - Li, Bowen; Wang, Zhiheng; Su, Shi‐Jian; Guo, Fengyun; Cao, Yong; Zhang, Yong
Abstract: The development of new and easily available acceptor moieties for further expansion of the thermally activated delayed fluorecence (TADF) family becomes imperative. In this study, new donor–acceptor TADF materials are designed and synthesized via introducing quinazoline unit as a simple and efficient acceptor for the first time. This is also a typical example of efficient spin–orbit charge transfer coupled between the acceptor triplet ( 3 LEA ) and charge transfer singlet ( 1 CT). The small 3 LE– 1 CT gap of 0.09–0.22 eV plays a key role in these four emitters leading to the obvious TADF properties. Moreover, these materials exhibit green to yellow‐green emission and high photoluminescence quantum yield of 67.5–81.0% in the 1, 3‐bis( N ‐carbazoly)benzene (CBP) host. Organic light‐emitting diodes using the doped emitters exhibit high external quantum efficiency of 16.0–20.5%. Abstract : Quinazoline unit as a simple and novel acceptor is introduced into thermally activated delayed fluorescence (TADF) materials for the first time. A series of new donor–acceptor TADF materials has been developed. They exhibit small 3 LEA – 1 CT gap of 0.09–0.22 eV and the obvious TADF properties. The external quantum efficiency of organic light‐emitting diodes using these emitters could be up to 20.5%.